2019
DOI: 10.3390/acoustics1010011
|View full text |Cite
|
Sign up to set email alerts
|

On the Frequency Up-Conversion Mechanism in Metamaterials-Inspired Vibro-Impact Structures

Abstract: Conventional acoustic absorbers like foams, fiberglass or liners are used commonly in structures for industrial, infrastructural, automotive and aerospace applications to mitigate noise. However, these have limited effectiveness for low-frequencies (LF, <~500 Hz) due to impractically large mass or volume requirements. LF content being less evanescent is a major contributor to environmental noise pollution and induces undesirable structural responses causing diminished efficiency, comfort, payload integrity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The combination of added linear and nonlinear dampers to an ABH beam is studied in [30], showing also important improvements toward broadband vibration mitigation. In related fields, other studies considered similar ideas and reported results, see for example the quadratic hysteretic nonlinearity characteristic of micro-inhomogeneous materials investigated in [31] for diminishing the wave speed, or the tuned mass-loaded membranes as vibro-impact attachments on a baseline structure in [32]. Nevertheless, all of these studies focus simply on the 1D beam case with a single type of nonlinearity.…”
Section: Introductionmentioning
confidence: 92%
“…The combination of added linear and nonlinear dampers to an ABH beam is studied in [30], showing also important improvements toward broadband vibration mitigation. In related fields, other studies considered similar ideas and reported results, see for example the quadratic hysteretic nonlinearity characteristic of micro-inhomogeneous materials investigated in [31] for diminishing the wave speed, or the tuned mass-loaded membranes as vibro-impact attachments on a baseline structure in [32]. Nevertheless, all of these studies focus simply on the 1D beam case with a single type of nonlinearity.…”
Section: Introductionmentioning
confidence: 92%
“…However, the prospect of using material systems with non-linear response characteristics for sound barrier applications was investigated only recently by Rekhy et al [17]. The authors studied both numerically and experimentally the characteristics of plate structures with a mass-loaded membrane and an impactor; thus creating a non-linear system, and the feasibility of shifting energy from lower frequencies to higher frequencies was demonstrated.…”
Section: Introductionmentioning
confidence: 99%